Pengaruh Sumber Daya dan Disposisi Pelaksana terhadap Implementasi Kebijakan pada Sekolah Ramah Anak di Surabaya - Maya Thersina; Muhamad Sholeh; Mufarrihul Hazin; Amrozi Khamid; Mochamad Nursalim (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the influence of resources and disposition of implementers on the implementation of the Child-Friendly School (SRA) policy in Surabaya. The method used is library research by analyzing various literature such as scientific journals, government regulations, and reports from related agencies. Data were collected through searching for relevant written documents in the last ten years and analyzed descriptively qualitatively. The results of the study indicate that the implementation of the SRA policy still faces various challenges, especially related to the limited number of trained educators, budget, and supporting facilities. In addition, the understanding, commitment, and motivation of policy implementers are also not optimal. Schools with better resources and disposition of implementers have proven to be more successful in implementing the SRA policy. This study recommends increasing the budget, intensive training, strengthening policy socialization, and support from local governments and educational organizations as strategic steps in supporting the effectiveness of the implementation of the Child-Friendly School policy.  Keywords: Resources, Disposition of Implementers, Literature Study, Policy Implementation